Comparative Analysis of Incidence and Outcomes of Acute Hepatitis A (HAV) and B Virus Infections (HBV) in Children Aged ≤ 20 years in the United States (US). (4th October 2017) - Edwards, Brett; Shaheen, Abdel Aziz; Parkins, Michael; Somayaji, Ranjani
Abstract: Background: HAV and HBV are amongst the most common vaccine preventable diseases and may be associated with morbidity and health care costs. The epidemiology and impact of acute HAV and HBV infection in pediatric hospitalizations is poorly defined relative to other populations. Methods: A cohort study was undertaken with the 2012 Kids' Inpatient Database that encompasses a stratified random sample of community and non-rehabilitation based hospitalizations across the US of pediatric patients aged ≤ 20 years. The primary outcome was incidence of acute HAV and HBV-related hospitalizations. Risk factors of age, sex, and race, and outcomes of length of stay (LOS), and costs were compared between persons with HAV and HBV infection. ICD-9 codes of 070.0–070.31 were utilized to capture acute HAV and HBV cases. Continuous and discrete outcomes between HAV and HBV were calculated with linear and logistic regression (with weighting), respectively. Results: A total of 424 cases of acute viral hepatitis A (48.3%), B (50.5%), and co-infection (1.2%) occurred, corresponding to a national overall incidence rate of 8.9 cases per 100, 000 persons (aged ≤ 20 years). HBV acquisition was associated with a higher mean age than HAV (15.4 vs. 13.1 years, P < 0.001). A greater proportion of patients with HBV compared with HAV were female (70.1% vs. 41.2%, P < 0.001). The distribution of race was significantly different with disproportionate numbers of HBV compared with HAV cases in Blacks and Asians ( P < 0.001). LOS (6.93 vs. 4.38 days, P = 0.02) and hospitalization costs (58, 211 vs. 30, 758, P = 0.03) were both significantly greater in HBV than HAV cases. Conclusion: We demonstrated that acute HAV and HBV cases differed in demographic factors of sex, age, and race, and that HBV was associated with greater LOS and costs. Although the incidence was low, enhanced vaccine efforts are indicated for further prevention of these infections in children. Disclosures: All authors: No reported disclosures.